Embryonic development in Zungaro jahu - Marques, Camila; Faustino, Francine; Bertolucci, Bruno; Paes, Maria Do Carmo Faria [UNESP]; Silva, Regiane Cristina Da [UNESP]; Nakaghi, Laura Satiko Okada [UNESP] (Cambridge University Press (CUP), 2017)
Summary The aim of this study was to characterize the embryonic development of Zungaro jahu, a fresh water teleostei commonly known as 'jaú'. Samples were collected at pre-determined times from oocyte release to larval hatching and analysed under light microscopy, transmission electron microscopy and scanning electron microscopy. At the first collection times, the oocytes and eggs were spherical and yellowish, with an evident micropyle. Embryo development took place at 29.4 ± 1.5°C and was divided into seven stages: zygote, cleavage, morula, blastula, gastrula, organogenesis, and hatching. The differentiation of the animal and vegetative poles occured during the zygote stage, at 10 min post-fertilization (mpf), leading to the development of the egg cell at 15 mpf. From 20 to 75 mpf, successive cleavages resulted in the formation of 2, 4, 8, 16, 32 and 64 blastomeres. The morula stage was observed between 90 and 105 mpf, and the blastula and gastrula stage at 120 and 180 mpf; respectively. The end of the gastrula stage was characterized by the presence of the yolk plug at 360 mpf. Organogenesis followed, with differentiation of the cephalic and caudal regions, elongation of the embryo by the cephalo-caudal axis, and somitogenesis. Hatching occurred at 780 mpf, with mean larval total length of 3.79 ± 0.11 mm.
Keywords: Embryo; Fish; Histology; Structure; Ultrastructure